Detection of Brucella antibodies in domestic animals of southern Cameroon: Implications for the control of brucellosis. Issue 3 (3rd April 2020) - Kamga, Rolin M. N.; Silatsa, Barberine A.; Farikou, Oumarou; Kuiate, Jules‐Roger; Simo, Gustave
Abstract: Brucellosis is one of the world's most widespread bacterial zoonoses caused by Brucella. It leads to considerable economic losses as a result of low productivity of infected animals and the long debilitating illness in humans. Despite its impact on human and animal health, little attention has been paid on Brucella infections in domestic animals. It is in this light that the prevalence of Brucella antibodies was determined in domestic animals with the overarching goal of improving our knowledge on brucellosis in southern Cameroon. During cross‐sectional studies conducted from December 2016 to August 2018 in five sites of southern Cameroon, blood samples were collected in cattle, sheep, goat, pig and dog. Plasma was obtained from each blood sample and Brucella antibodies were detected using the Rose Bengal test and the enzyme‐linked immunosorbent assay (ELISA). From 1873 animals that were sampled, the overall prevalence of Brucella antibodies using Indirect enzyme‐linked immunosorbent assay (i‐ELISA) was 6.35% (118/1873): 9.12% (78/855) in cattle; 8.04% (30/373) in sheep; 6.06% (2/33) in dog, 1.87% (3/160) in pig and 1.1% (5/452) in goat. Between animal species ( p ‐value < .0001, x 2 = 33.63) as well as sampling sites ( p ‐value = .0001, x 2 = 18.97), significant differences were observed in the prevalence of Brucella antibodies. Yoko and Noun localities have shown the highest prevalence of 8.6% (30/348) and 7.2% (78/1070), respectively. This prevalence was significantly higher ( p = .03, x 2 = 1.25) in female than male cattle. Between adult (16.923%) and young cattle (7.8%), significant difference ( p = .04, x 2 = 6.42) was observed in the prevalence of Brucella antibodies. This study shows that the prevalence of Brucella antibodies varies between animal species and localities. It also shows several domestic animals of southern Cameroon that have been in contact with Brucella . It enabled to identify villages where investigations on the transmission dynamic must be focused for the final goal of developing control measures for this neglected zoonotic disease. Abstract : Brucella infections can affect cattle, pigs, sheep, goats and dogs;As the results of Brucella infections, the prevalence Brucella antibodies varies not only between animal species, but also between localities for which each of them has specific environmental conditions;Understanding the epidemiology of brucellosis for the overarching objective of designing efficient control measures requires investigating such infections on human and animal in different epidemiological settings.